Isolated Retrobulbar Orbital Hydatid Cyst: A Rare Case Report (Bangladesh Journal of Medical Science, 2013)
Isolated orbital hydatid cyst is a rare manifestation most commonly situated in superomedial and superolateral angles of orbit. We report a case of a 24 years old female with a large retrobulbar orbital hydatid cyst causing proptosis which was not associated with any cyst in other organs. USG and CT scan aids to diagnosis while surgical excision and histopathology confirms the diagnosis. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 220-223 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14976